Problematização do patrimônio arquitetônico de Bragança no ensino de geometria - CUNHA, Eliana Catarina Farias (2020)
The teaching of geometry in the early years can be a priority in teaching, focusing on developing in students the skills necessary to understand the context in which they live. Thus, this work aims to propose geometry teaching activities for the early years of elementary school based on the problematization of Bragança's architectural and socio-cultural heritage. This is a qualitative research that had a bibliographic survey focusing on official curriculum documents, results of research already carried out on the theme in theoretical foundations for the work that comes from the ideas of Miguel and Mendes (2010) and Farias. and Mendes on the teaching of mathematics through artifacts of culture. The results indicate that the old buildings of Bragança, Pará, when subjected to problematization may provide elements that refer to the flat geometry of the early years of elementary school, which may favor the learning of this geometry by students of this level.